2x2+3√5x+5 = 2x2 + 2√5x+ √5x+5
= 2x (x + √5) +√5 (x+√5)
= (2x+√5) (x+√5)
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
RELATED QUESTIONS :
75×75+2×RD Sharma - Mathematics
If x+<span lang="RD Sharma - Mathematics
If a1RD Sharma - Mathematics